PERENCANAAN PROGRAM MOTIVASI BANGUN DARI MIMPI BUKAN BERARTI TIDAK BISA BERMIMPI KEMBALI - Halalah Amaliyah; Isnani Nurpazriah; Nur Fadiyah Khaerunnisa; Ridha Syahnai; Shofin Muhammad; Yuli Sri Awaliyah (Jurnal Pengabdian Masyarakat Indonesia, 2023)
The Center for Community Learning Activities (PKBM) is a non-formal educational institution that organizes several programs, one of which is the equality program or pursuing packages. Package A is equivalent to SD, Package B is equivalent to SMP, and Package C is equivalent to SMA. Non-formal education has a function as a substitute, complement, and enhancer. Motivation can be defined as something within oneself that drives activities to achieve certain goals. a Motivational Talk Show program with the theme "Waking up from a Dream Doesn't Mean You Can't Dream Again" motivates learning residents. In this case the learning residents participate well as evidenced by the learning residents asking questions. This shows that this program gets the attention of the learning community and increases their learning motivation. Through this activity the AL-FATTAH PKBM learning residents get knowledge and information related to scholarships which are usually at the tertiary level or in lectures. Because scholarships are grants issued by the government for underprivileged students or students and for those who have high achievements to continue their studies at the university level. Scholarships are defined as a form of appreciation given to individuals so they can continue their education to a higher level.